2012
DOI: 10.1128/jb.01821-12
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Burkholderia phenoliruptrix BR3459a (CLA1), a Heat-Tolerant, Nitrogen-Fixing Symbiont of Mimosa flocculosa

Abstract: The genus Burkholderia represents a challenge to the fields of taxonomy and phylogeny and, especially, to the understanding of the contrasting roles as either opportunistic pathogens or bacteria with biotechnological potential. Few genomes of nonpathogenic strains, especially of diazotrophic symbiotic bacteria, have been sequenced to improve understanding of the genus. Here, we contribute with the complete genome sequence of Burkholderia phenoliruptrix strain BR3459a (CLA1), an effective diazotrophic symbiont … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Lebeckia spp. ), such as B. dilworthii and B. sprentiae, which was to be expected in consideration of other reports [14][15][16]41,61]. Also reported that the fixNOQP and fixGHIS nitrogenase production and assembly genes are missing in all the Burkholderia strains that they examined, but after further analysis of the products of these genes we found their protein products were annotated on the published genome for B. phymatum STM815 T , but there were no relevant annotation gene names in GenBank.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Lebeckia spp. ), such as B. dilworthii and B. sprentiae, which was to be expected in consideration of other reports [14][15][16]41,61]. Also reported that the fixNOQP and fixGHIS nitrogenase production and assembly genes are missing in all the Burkholderia strains that they examined, but after further analysis of the products of these genes we found their protein products were annotated on the published genome for B. phymatum STM815 T , but there were no relevant annotation gene names in GenBank.…”
Section: Discussionmentioning
confidence: 84%
“…In parallel, in South Africa, the papilionoid tribes associated with the South African Burkholderias, Crotalarieae and Podalyrieae, arose [44][45][46], and these plants also presumably encountered the acid-loving Burkholderia as they colonized and speciated within the acidic soils of the Fynbos. The main differences between the nodulating Burkholderias in South America and those of their South African cousins is that the former have very different nod genes to local Alpha-rhizobia [61], whereas the latter nodulate a wide range of Fynbos legume genera which are often also capable of nodulating with Alpharhizobia, such as Mesorhizobium [14][15][16]. This most likely explains why the nod genes of the South African Burkholderias are so similar to those of Alpha-rhizobia, but it does not tell us which came first and who transferred them to WHO.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations